2002
DOI: 10.1108/13639510210417890
|View full text |Cite
|
Sign up to set email alerts
|

Community‐oriented policing in Germany

Abstract: Presents data from two surveys and arguments in favour of a restructuring of the police service, in general, and police training in particular. Contends that to keep up with an everchanging world, the police has to become more versatile itself, without losing sight of its core functions: protection and security provision. These objectives can only be achieved by a police force that cooperates intensively with the people, i.e. relies on a community-oriented approach to policing, and one whose members have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 4 publications
0
27
0
Order By: Relevance
“…The Dutch use a dual system of education and training in 9 order to facilitate clear links between theory and practice (Peeters, 2010). Feltes's (2002) work in Germany emphasizes the importance of communication and conflict resolution skills alongside the traditional focus on the law for community-oriented police. Feltes also stresses the emphasis placed upon criminological theory within German institutions.…”
Section: The European Union (Eu)mentioning
confidence: 99%
See 1 more Smart Citation
“…The Dutch use a dual system of education and training in 9 order to facilitate clear links between theory and practice (Peeters, 2010). Feltes's (2002) work in Germany emphasizes the importance of communication and conflict resolution skills alongside the traditional focus on the law for community-oriented police. Feltes also stresses the emphasis placed upon criminological theory within German institutions.…”
Section: The European Union (Eu)mentioning
confidence: 99%
“…The police discipline adds value to police training by enabling senior police officers to make sense of developments in transnational crime, social exclusion, terrorism, public demand for transparency, and a shift to proactive intelligence-led policing supported by an international research agenda. Yet, while research has demonstrated the value of higher education upon officer attitudes (Lee and Punch, 2004), little empirical research has been conducted on the impact of higher education on behavior and police performance (Feltes, 2002;Jaschke, 2010).…”
Section: The European Union (Eu)mentioning
confidence: 99%
“…The large and varied nature of the literature leaves a wide body of work to draw on, but a difficult landscape to navigate. Existing work relevant to this study includes that which looks particularly at change in large complex public sector organisations and especially police organisations (Duncan, Mouly et al 2001, Feltes 2002, Densten 2003, Ellison 2007, Pettigrew 2012. The RUC experience as explored here is an examination of 'radical' organisational change -a transformatory shift from one organisational form to another (McNulty and Ferlie 2004).…”
Section: A Note On the Process Lens Perspectivementioning
confidence: 99%
“…Equal weighting must be afforded to the teaching of the unique skills required in community policing as to the teaching of the law enforcement skills associated with crime-driven policing. An emerging community-oriented police means PIJPSM 29,2 that communication skills and conflict resolution abilities must have the same importance as knowledge of the law (Feltes, 2002).…”
Section: Ipldp and The Future Of Probationer Trainingmentioning
confidence: 99%
“…The payoff from this will be an improved product in terms of the The current issue and full text archive of this journal is available at www. emeraldinsight.com/1363-951X.htm Training for neighbourhood policing 335 resultant quality of policing (Feltes, 2002). In order to expedite the continued evolution of the police service into a profession committed to a community-focused approach, it is important to identify and adopt the most appropriate methods to facilitate this transition (Birzer and Nolan, 2002).…”
Section: Introductionmentioning
confidence: 99%